2021
DOI: 10.1155/2021/2105176
|View full text |Cite|
|
Sign up to set email alerts
|

mRNA Network: Solution for Tracking Chemotherapy Insensitivity in Small-Cell Lung Cancer

Abstract: Background. Small-cell lung cancer (SCLC) has poor prognosis and is prone to drug resistance. It is necessary to search for possible influencing factors for SCLC chemotherapy insensitivity. Therefore, we proposed an mRNA network to track the chemotherapy insensitivity in SCLC. Methods. Six samples of patients with SCLC were recruited for RNA sequencing. TopHat2 and Cufflinks were used to make differential analysis. Functional analysis was applied as well. Finally, multidimensional validation was applied for ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…However, no research studies were found to concentrate on the relationship between LUAD with the other eight genes: HGSNAT, ENPP5, MCTP2, PLEKHA6, ANKRD29, ZNF738, SLC4A5, and CNTNAP2. ENPP5, MCTP2, PLEKHA6, ANKRD29, SLC4A5, and CNTNAP2 were shown to play a role in malignancy other than NSCLC ( Bralten et al, 2010 ; Langevin et al, 2012 ; Smith et al, 2012 ; Parris et al, 2014 ; Yang and Loh, 2019 ; Gopalakrishnan et al, 2020 ; Song et al, 2020 ; Sun et al, 2020 ; Chen et al, 2021b ). No previous research studies were published concerning the relationship between cancer and HGSNAT or ZNF738.…”
Section: Discussionmentioning
confidence: 99%
“…However, no research studies were found to concentrate on the relationship between LUAD with the other eight genes: HGSNAT, ENPP5, MCTP2, PLEKHA6, ANKRD29, ZNF738, SLC4A5, and CNTNAP2. ENPP5, MCTP2, PLEKHA6, ANKRD29, SLC4A5, and CNTNAP2 were shown to play a role in malignancy other than NSCLC ( Bralten et al, 2010 ; Langevin et al, 2012 ; Smith et al, 2012 ; Parris et al, 2014 ; Yang and Loh, 2019 ; Gopalakrishnan et al, 2020 ; Song et al, 2020 ; Sun et al, 2020 ; Chen et al, 2021b ). No previous research studies were published concerning the relationship between cancer and HGSNAT or ZNF738.…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%